THE TRANSLATION STRATEGIES OF IDIOMS FOUND IN THE BOSS BABY: BACK IN BUSINESS MOVIE SERIES - Tambunan, Sunarti Desrieny (UG Journal, 2021)
Idioms are fixed combinations of words whose meaning cannot be determined by looking at theexpression itself. Moreover, identifying whether the phrase or clause is an idiom or not is alsodifficult to do unless the translator is familiar with the expressions. This research aims at findingthe translation strategies in translating the idioms found in The Boss Baby: Back in BusinessMovie Series, Season 2, Episodes 1-3. This research is a descriptive qualitative. Observationmethod and note taking were applied in order to collect the data and achieve the aim of theresearch. The results show that there are 20 idioms found in the three episodes. The strategiesused in Episode 1, entitled As the Diaper Changes, are an idiom with dissimilar form strategy (1),paraphrasing (5), and omission (1). Episode 2, entitled Super Cool Big Kids Inc., an idiom withsimilar meaning and form (1), and paraphrasing (5). Episode 3 entitled P.U., paraphrasing (7).